2023
DOI: 10.1002/biot.202300283
|View full text |Cite
|
Sign up to set email alerts
|

Rapid construction of Escherichia coli chassis with genome multi‐position integration of isopentenol utilization pathway for efficient and stable terpenoid accumulation

Abstract: The isopentenol utilization pathway (IUP) is potential in terpenoids synthesis. This study aimed to construct IUP‐employed Escherichia coli chassis for stably synthesizing terpenoids. As to effectiveness, promotor engineering strategy was employed to regulate IUP expression level, while ribosome‐binding site (RBS) library of the key enzyme was constructed for screening the optimal RBS, followed by optimization of concentration of inducer and substrates, the titer of reporting production, lycopene, from 0.087 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In future, genomic integration of biosynthetic pathways is strongly recommended for construction of robust and efficient cell factory, which can be aided by characterizing genomic integrations sites for gene expression without affecting the cell fitness. [32][33][34][35] Proteomic analysis of engineered strain with the control strain showed that the key metabolic enzymes of the central metabolic pathways were significantly up-regulated, which suggested that sabinene biosynthesis pulled the metabolic flux from glycolysis toward MVA pathway. Interestingly, we found the dual pathway in mitochondria and cytosol (strain 64) was better than the duplicated pathway in mitochondria (strain 67).…”
Section: Discussionmentioning
confidence: 99%
“…In future, genomic integration of biosynthetic pathways is strongly recommended for construction of robust and efficient cell factory, which can be aided by characterizing genomic integrations sites for gene expression without affecting the cell fitness. [32][33][34][35] Proteomic analysis of engineered strain with the control strain showed that the key metabolic enzymes of the central metabolic pathways were significantly up-regulated, which suggested that sabinene biosynthesis pulled the metabolic flux from glycolysis toward MVA pathway. Interestingly, we found the dual pathway in mitochondria and cytosol (strain 64) was better than the duplicated pathway in mitochondria (strain 67).…”
Section: Discussionmentioning
confidence: 99%
“…In order to simultaneously introduce the dual-enzyme combination RBS mutation library into the cascade reaction, it is necessary to design and obtain the RBS mutation sequence of each gene separately. The translation initiation rates of fully degenerate sequences at the SD of gene adh and chmo were calculated using the RBS combinatorial library Calculator [39][40][41][42] in predict version 2.0, respectively. The SD sequence-TIR data set of the ADH gene (translation initiation rates (TIRs) ranging from 5 to 8234 arbitrary units, with the TIR of the wild type RBS predicted at 16916) and the SD sequence-TIR data set of the CHMO gene (translation initiation ratios (TIRs) ranging from 10619 to 106120 arbitrary units, with the TIR of the wild type RBS predicted at 16610) were used as input for the Redlibs algorithm, respectively, where the library sizes were set to 24 library variants and the target distribution was set to a uniform distribution between the minimal and maximal values of each input library (Table S2).…”
Section: Rbs Combinatorial Library Design and Constructionmentioning
confidence: 99%